Web Archive Search as Research: Methodological and Theoretical Implications. Issue 1 (August 2014) - Ben-David, Anat; Huurdeman, Hugo
The field of web archiving is at a turning point. In the early years of web archiving, the single URL has been the dominant unit for preservation and access. Access tools such as the Internet Archive's Wayback Machine reflect this notion as they allowed consultation, or browsing, of one URL at a time. In recent years, however, the single URL approach to accessing web archives is being gradually replaced by search interfaces. This paper addresses the theoretical and methodological implications of the transition to search on web archive research. It introduces 'search as research' methods, practices already applied in studies of the live web, which can be repurposed and implemented for critically studying archived web data. Such methods open up a variety of analytical practices that were so far precluded by the single URL entry point to the web archive, such as the re-assemblage of existing collections around a theme or an event, the study of archival artefacts and scaling the unit of analysis from the single URL to the full archive, by generating aggregate views and summaries. The paper introduces examples to 'search as research' scenarios, which have been developed by the WebART project at the University of Amsterdam and the Centrum Wiskunde & Informatica, in collaboration with the National Library of the Netherlands. The paper concludes with a discussion of current and potential limitations of 'search as research' methods for studying web archives, and the ways with which they can be overcome in the near future.